Optimal Ir/Pt ratio for the ring opening of decalin in zeolite supported catalysts - D'ippolito, Silvana Andrea (2012)
The aim of this study was to study the ring opening of decalin at 300 and 350 °C using Pt-Ir/HY zeolite catalysts. Monometallic Ir(x = 1.0, 1.5%wt) and Pt(y = 1.0, 1.5%wt) and bimetallic Ir(1.0)Pt(y = 0.5, 1.0, 1.5%wt), Ir(1.5)Pt(y = 0.5, 1.0, 1.5%wt) catalysts were prepared and catalytically tested. Catalysts were characterized by TPR, pyridine TPD, CO-FTIR, cyclohexane dehydrogenation and cyclopentane hydrogenolysis activity. It was found that the acidic character of Ir oxides species increased the amount of strong acid sites of the support. On the other hand, the Pt content increase favored the formation of medium strength acid sites. The catalysts with higher content of Ir had the higher hydrogenolytic activity, while an increase in the Pt content decreased the hydrogenolytic activity. The presence of Pt promoted the dehydrogenation of cyclohexane. Higher yields of dehydrogenated products and increased conversion of cis-decalin were observed at the highest temperature level. It seems that catalysts Ir(1.0)Pt(1.0) at 350 °C and Ir(1.5)Pt(1.5) at 300 °C, which showed a good performance, have an adequate balance between metal and acid functions that favors the opening of naphthenic rings.